Navigational Transmaxillary Endoscopic Approach for Inferomedial Tumors - Cheng-Hsien Wu; Cheng-Hsien Wu; Yi-Yun Ho; Tzu-Lun Liu; Tzu-Ying Wu; Tzu-Ying Wu; Han-Chieh Cheng; Han-Chieh Cheng; Chieh-Chih Tsai; Chieh-Chih Tsai (Frontiers in Oncology, 2022)
Orbital tumors encompass a heterogeneous range of histopathology and usually variable in location. Traditionally, transconjunctival medial orbitotomy is used to access the medial orbital wall. However, it creates potential risk of soft tissue sequelae such as scarring, lid contracture, or entropion/ectropion. For the lesions close to the orbital apex, increased risk of optical nerve injury should be cautious during orbitotomy procedure. Transnasal endoscopic approach to the orbital walls has been applied since 1999. Although it provides good surgical visualization and prevents the soft tissue and neural complications, the narrow nasal corridor increases the surgical complexity. Extensive sphenoethmoidectomy is usually required to gaining access. Furthermore, the resultant medical orbital defect is difficult to repair. The maxillary sinus is the largest paranasal sinuses which is located beneath the orbital floor. It provides an ample working space for instrumentation. Meanwhile, repair of the orbital floor defect is feasible and with high degree of accuracy under navigation control. In this report, we propose a novel computer-assisted endoscopic protocol to excise the medial orbital tumors with immediate repair of the wall defect.